1982
DOI: 10.1080/02786828208958582
|View full text |Cite
|
Sign up to set email alerts
|

Coal Combustion Aerosol Formation Mechanisms: A Review

Abstract: The composition and size distribution of particles data regarding fly ash size distribution and elemental emitted by coal combustion sources depend upon concentrations in various size fractions were analyzed. various mechanisms leading to their formation. A These data were qualitatively compared with theoretical review of current ideas about possible mechanisms for model predictions to indicate the relative contributions formation of combustion aerosols is presented. Available of various mechanisms in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…Other studies have shown an enrichment of the smaller particle sizes in the trace volatile elements. 21,54,60,61,66,[69][70][71][72][74][75][76][77][78][79][80][81][82][83][84] The reasons for attention to the size dependence of trace element concentration are that (1) this provides a diagnostic for the mechanism of surface deposition; (2) the enrichment of submicron particles in certain elements affects the total capture efficiency of that element in the APCDs; and (3) elemental concentrations affect the chemical speciation, which can be important for health effects.…”
Section: Particle (Soot) Inception By Chemical Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown an enrichment of the smaller particle sizes in the trace volatile elements. 21,54,60,61,66,[69][70][71][72][74][75][76][77][78][79][80][81][82][83][84] The reasons for attention to the size dependence of trace element concentration are that (1) this provides a diagnostic for the mechanism of surface deposition; (2) the enrichment of submicron particles in certain elements affects the total capture efficiency of that element in the APCDs; and (3) elemental concentrations affect the chemical speciation, which can be important for health effects.…”
Section: Particle (Soot) Inception By Chemical Reactionmentioning
confidence: 99%
“…Sodium, for example, will have its vaporization suppressed either because it may be originally present in sodium aluminosilicates or because it is captured by the alumina silicates after release. [65][66][67] Particle Growth by Condensation and Surface Reaction Vaporized elements distribute on the surfaces of existing submicron and residual ash particles by condensation and chemical reaction. The rate of mass addition to a spherical particle for mass-transfer limited deposition over the entire range of particle size is given by the Fuchs-Sutugin interpolation equation:…”
Section: Particle (Soot) Inception By Chemical Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, all important governing parameters in the aerosol emissions equation are not well understood. It is generally accepted that conversion of mineral species in the coal to fly ash can follow at least two paths (e.g., Flagan and Friedlander, 1978;Damle et al, 1982). First, the major inclusions can soften and melt during the burning of the char particle (relatively little ash is given off during the coal devolatilization process), and some then coalesce as the char support structure bums away.…”
Section: Introductionmentioning
confidence: 99%
“…A large particle mode is formed by the coalescence of mineral inclusions in the char and a fine particle mode is formed by a vaporization and condensation mechanism (Damle, Ensor et al 1982). The fine particles have a different bulk composition than the large particles and the structure is layered with the surface enriched in volatile elements (Neville and Sarofim 1982;Linak and Wendt 1994).…”
Section: Introductionmentioning
confidence: 99%